Overview of MAN Student's Preceptions of Early Marriage: Gambaran Persepsi Siswa MAN Terhadap Pernikahan Dini - Siregar, Nilda Yulita; Ramadhan, Kadar; Mirna, Mirna (Poltekkes Kemenkes Palu, 2023)
Background: In MAN 1 Poso there are still students who have dropped out of school due to early marriage. Adolescent life is a life that is very decisive for one's future. Objective: to find out how students perceive early marriage in MAN 1 Poso, Poso Pesisir District, Poso Regency.Method: the type of research used in this study is a descriptive type research method. The population used in this study was MAN 1 Poso students i.e. 408 students. The sample in this study was 80 respondents, the technique of determining the sample by simple random sampling is a technique to select sample members from population members so that population members have the same opportunity to become sample members. Results: showed that MAN 1 Poso, based on the results of research on the cognitive aspects of respondents about early marriage in general was good for as many as 58 students (72.5%). Based on the results of research on the affective aspects of respondents showed as many as 44 students (55%) did not support early marriage. On the conative aspect, respondents stated that they did not agree with the existence of early marriage as many as 50 students (62.5%).Conclusion: Based on cognitive, affective, and conative aspects, the majority of respondents are well informed, do not support early marriage, and are not ready to face the condition. The researchers' suggestion is that the school will continue to provide counseling to students related to early marriage and conduct counseling by health workers and other related parties and the school will establish a youth counseling information center program.